2001
DOI: 10.1117/12.447124
|View full text |Cite
|
Sign up to set email alerts
|

<title>Determination of the optical parameters of dentin from spatially resolved reflectance and transmittance measurements</title>

Abstract: Measurements of the absolute spatially resolved reflectance and transmittance from dentin slabs were performed using a HeNe laser at λ = 633 mm as source and a CCD camera as detector. Solid phantom slabs were used to test the experimental setup and to enable absolute measurements. The reduced scattering and absorption coefficients were derived by applying a solution of the diffusion theory for a slab geometry as theoretical model. Monte Carlo simulations were used to investigate the validity of the diffusion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In many studies, the tissue sample can be assumed as isotropic, i.e., its optical properties are independent of photon incident directions. However, this is not true in some biological tissues such as muscle [1], skin [2], dentin [3], and white matter [4], where anisotropic fibrous or tubular structures are abundant. For example, Marquez et al [1] found that optical properties of the chicken breast differed significantly when measured parallel or perpendicular to the muscle fiber orientation.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, the tissue sample can be assumed as isotropic, i.e., its optical properties are independent of photon incident directions. However, this is not true in some biological tissues such as muscle [1], skin [2], dentin [3], and white matter [4], where anisotropic fibrous or tubular structures are abundant. For example, Marquez et al [1] found that optical properties of the chicken breast differed significantly when measured parallel or perpendicular to the muscle fiber orientation.…”
Section: Introductionmentioning
confidence: 99%